Nernst–Planck–Gaussian finite element modelling of Ca2+ electrodiffusion in amphibian striated muscle transverse tubule–sarcoplasmic reticular triadic junctional domains - Rodríguez, Marco D.; Morris, Joshua A.; Bardsley, Oliver J.; Matthews, Hugh R.; Huang, Christopher L.-H. (Frontiers in Physiology, 2024)
IntroductionIntracellular Ca2+ signalling regulates membrane permeabilities, enzyme activity, and gene transcription amongst other functions. Large transmembrane Ca2+ electrochemical gradients and low diffusibility between cell compartments potentially generate short-lived, localised, high-[Ca2+] microdomains. The highest concentration domains likely form between closely apposed membranes, as at amphibian skeletal muscle transverse tubule–sarcoplasmic reticular (T-SR, triad) junctions.Materials and methodsFinite element computational analysis characterised the formation and steady state and kinetic properties of the Ca2+ microdomains using established empirical physiological and anatomical values. It progressively incorporated Fick diffusion and Nernst–Planck electrodiffusion gradients, K+, Cl−, and Donnan protein, and calmodulin (CaM)-mediated Ca2+ buffering. It solved for temporal–spatial patterns of free and buffered Ca2+, Gaussian charge differences, and membrane potential changes, following Ca2+ release into the T-SR junction.ResultsComputational runs using established low and high Ca2+ diffusibility (DCa2+) limits both showed that voltages arising from intracytosolic total [Ca2+] gradients and the counterions little affected microdomain formation, although elevated DCa2+ reduced attained [Ca2+] and facilitated its kinetics. Contrastingly, adopting known cytosolic CaM concentrations and CaM-Ca2+ affinities markedly increased steady-state free ([Ca2+]free) and total ([Ca2+]), albeit slowing microdomain formation, all to extents reduced by high DCa2+. However, both low and high DCa2+ yielded predictions of similar, physiologically effective, [Ca2+-CaM]. This Ca2+ trapping by the relatively immobile CaM particularly increased [Ca2+] at the junction centre. [Ca2+]free, [Ca2+-CaM], [Ca2+], and microdomain kinetics all depended on both CaM-Ca2+ affinity and DCa2+. These changes accompanied only small Gaussian (∼6 mV) and surface charge (∼1 mV) effects on tubular transmembrane potential at either DCa2+.ConclusionThese physical predictions of T-SR Ca2+ microdomain formation and properties are compatible with the microdomain roles in Ca2+ and Ca2+-CaM-mediated signalling but limited the effects on tubular transmembrane potentials. CaM emerges as a potential major regulator of both the kinetics and the extent of microdomain formation. These possible cellular Ca2+ signalling roles are discussed in relation to possible feedback modulation processes sensitive to the μM domain but not nM bulk cytosolic, [Ca2+]free, and [Ca2+-CaM], including ryanodine receptor-mediated SR Ca2+ release; Na+, K+, and Cl− channel-mediated membrane excitation and stabilisation; and Na+/Ca2+ exchange transport.